Electrospun hydrolyzed collagen from tanned leather shavings for bio-triboelectric nanogenerators. Issue 12 (27th May 2022) - Li, Lingyan; Zhang, Jian; Wang, Manting; Zhang, Jiaqi; Zeng, Xiao-Fei; Wang, Jie-Xin; Le, Yuan
Abstract : Triboelectric nanogenerators (TENGs) have become a research hotspot as feasible energy harvesters because they can efficiently convert mechanical energy into electrical output for energy supply, showing advantages in micro-scale energy harvesting for applications in portable devices. Abstract : Triboelectric nanogenerators (TENGs) have become a research hotspot as feasible energy harvesters because they can efficiently convert mechanical energy into electrical output for energy supply, showing advantages in micro-scale energy harvesting for applications in portable devices. Herein, we employed collagen extracted from leather shavings to fabricate an all-nanofiber bio-TENG via a cost-effective electrospinning technique. By optimizing the spinning parameters, flexible and stretchable collagen/PVA/Ag NW composite nanofiber films were successfully fabricated. The as-prepared film exhibited remarkable antibacterial activity and biocompatibility. The designed bio-TENG, using a collagen-based film and an electrospun PVDF film as the top and bottom triboelectric layers, displayed excellent electrical output performance benefiting from the rougher surface and high porosity of the contact surface. The bio-TENG can serve as a reliable power source to drive lower-power electronics. This research provides a simple and economical strategy to utilize the waste biomaterial for the construction of the bio-TENG and proposes a promising idea in the design of mechanical energy harvesters to supply low-power devices.